Measurement of Zakat Impact on Baitul Maal Hidayatullah: Evidence from Indonesia (ZISWAF: Jurnal Zakat dan Wakaf, 2021)
Zakat is the third pillar of Islam that must be fulfilled by every Muslim who has a sufficient amount of zakat. The purpose of zakat management is to increase the benefits of zakat in creating social welfare and poverty alleviation. This study aims to measure the impact of zakat on the welfare of mustahiq using the Center of Islamic Business and Economic Studies (CIBEST) model. The research sample consisted of mustahiq households who received zakat funds from the Baitul Maal Hidayatullah Amil Zakat Institute (LAZ BMH). Measuring the impact of zakat using the CIBEST model includes both material and spiritual aspects. The primary data were collected using a questionnaire. The results of the study found that the mustahiq household welfare index value increased by 11.5 per cent. In terms of material, productive zakat succeeded in reducing material poverty by 11.5 per cent. However, the zakat assistance provided does not have a significant effect on poverty alleviation. In the spiritual aspect, productive zakat can maintain mustahiq's spiritual stability. Therefore, as a form of accountability, both vertically and horizontally, to Allah SWT, the impact of zakat must be increased from both material and spiritual aspects.